“Change is constant in today’s business for competitive advantage. Strategic leadership is vital for effective strategic change management - roles & responsibilities and strategic capability of strategic leadership.” - Chia, Grace Hui Yen (2009)
The aim of this paper is to seek to understand the reachange is constant in today’s business for competitive advantage. And to make the strategic change happen in order to achieve the desired outcome, what will be the right strategic process flow. What are the key challenges that will be encountered throughout the process of strategic change management? This paper will also learn whether strategic leadership is vital to make the strategic change happen in the effective way since many literatures are supporting this view and what will be their strategic roles and responsibilities. Besides, this research will also urge to learn whether everyone can be the strategic leader and what are the strategic capabilities of a strategic leader.This research is conducted in through the qualitative methodology via case study approach. Six (6)samplings were conducted from difference backgrounds of industries including a change agent of a Malaysia incorporated foreign companies. The qualification of the interviewees is important to ensure the quality and reliability of the data collection.